Valuation risk revalued - Oliver De Groot; Alexander W. Richter; Nathaniel A. Throckmorton (Quantitative Economics, 2022)
This paper shows the success of valuation risk-time-preference shocks in Epstein-Zin utility-in resolving asset pricing puzzles rests sensitively on the way it is introduced. The specification used in the literature is at odds with several desirable properties of recursive preferences because the weights in the time-aggregator do not sum to one. When we revise the specification in a simple asset pricing model the puzzles resurface. However, when estimating a sequence of increasingly rich models, we find valuation risk under the revised specification consistently improves the ability of the models to match asset price and cash-flow dynamics.
Keywords: C15; D81; G12; 330; Recursive utility; asset pricing; equity premium puzzle; risk-free rate puzzle